Changes in inner retinal layer thickness in patients with exudative age-related macular degeneration during treatment with anti-vascular endothelial growth factor. Issue 17 (April 2020) - Lee, Seong Woo; Sim, Ha Eun; Park, Jae Yong; Kim, Jae Suk; Chang, In Beom; Park, Young Soon; Hwang, Je Hyung
Abstract : Abstract: The aim of this study was to identify any changes that occur in the retinal nerve fiber layer (RNFL) and ganglion cell-inner plexiform layer (GC-IPL) in patients with exudative age-related macular degeneration (AMD) during treatment with anti-vascular endothelial growth factor (VEGF) injections. Patients were enrolled in this retrospective study if they had exudative AMD, had received at least 3 injections of ranibizumab or aflibercept, and had a minimum of 12 months of follow-up. We analyzed the changes in the RNFL and GC-IPL using spectral-domain optical coherence tomography in rescan mode. Fifty-two eyes of 52 patients who had been treated with repeated anti-VEGF injections for exudative AMD were included. At the final visit, there was no significant between-group difference in best-corrected visual acuity or intraocular pressure. There was a significant decrease in central macular thickness in all groups ( P < .05). There was a decrease in RNFL thickness that was only statistically significant in the ranibizumab group and when the ranibizumab or aflibercept groups were combined ( P = .036 and .044, respectively). The thickness of the GC-IPL layer was significantly decreased in the aflibercept and total group ( P = .035 and P = .048, respectively). The thicknesses of the RNFL and GC-IPL decreased in patients with exudative AMD who underwent repeated anti-VEGF injections.